Juan Medrano service awardees for 1998-1999 - Dizon, Rolando R., FSC (Animo Repository, 1999)
The awarding ceremony of the Juan Medrano Service Awardees for 1998-1999 was held following the Holy Mass celebrated by Community Chaplain Fr. Virgil Fabriquel. Bro. Rolando Dizon, FSC, delivered the homily.